Keselarasan Pendidikan Akhlak dan Ekspresi Kreatif Digital Peserta Didik Madrasah - Didit Darmawan; Irfan Nofa Sagita (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study conducts a literature review on the reconstruction of akhlakul karimah in the digital era, focusing on two main issues: the alignment between teacher guidance, school rules, and social media ethics, and the development of a digital akhlak portfolio for madrasah students as a creative expression of character education outcomes. Using a qualitative library research approach with content analysis, this study synthesizes relevant literature to build a theoretical framework. The findings indicate that successful character formation requires expanding the meaning of classical values into the digital realm, reforming school rules to explicitly regulate digital behavior, and the presence of teachers as role models in cyberspace. Furthermore, the digital akhlak portfolio concept positions social media as a platform for students to showcase creative works such as writing, visual arts, and videos that reflect internalized moral values. This portfolio serves as authentic documentation of character development, an evaluation tool, a creative da'wah medium, and a means of building the madrasah's positive reputation. The study contributes theoretically by integrating classical moral education theories with contemporary digital ethics and offers practical guidance for madrasahs to create a holistic educational ecosystem bridging the physical and digital worlds.